2000
DOI: 10.4049/jimmunol.164.6.3079
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Transplantation in Miniature Swine. II. Induction of Tolerance by Transplantation of Composite Thymokidneys to Thymectomized Recipients

Abstract: Previous studies in our laboratory have demonstrated that the presence of the thymus is essential for rapid and stable tolerance induction in allotransplant models. We now report an attempt to induce tolerance to kidney allografts by transplanting donor thymic grafts simultaneously with the kidney in thymectomized recipients. Recipients were thymectomized 3 wk before receiving an organ and/or tissues from a class I-mismatched donor. Recipients received 1) a kidney allograft alone, 2) a composite allogeneic thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 42 publications
2
112
2
1
Order By: Relevance
“…Medical thymic regeneration, combined with VTL transplantation, could move our tolerance induction regimen one step closer to the clinic by regenerating aged thymus either before or after VTL transplantation into an aged recipient. This strategy could have practical implications for extending thymus-dependent tolerance-inducing protocols (5,12,13,(30)(31)(32) to adult patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical thymic regeneration, combined with VTL transplantation, could move our tolerance induction regimen one step closer to the clinic by regenerating aged thymus either before or after VTL transplantation into an aged recipient. This strategy could have practical implications for extending thymus-dependent tolerance-inducing protocols (5,12,13,(30)(31)(32) to adult patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-embedded tissue was stained by using H&E. Coded samples were examined through a light microscope by a pathologist. Frozen samples were prepared for immunohistochemical analysis with the avidin-biotin horseradish-peroxidase complex technique (30). Thymopoiesis was assessed by immunohistochemistry by using the swine-specific murine mAbs described above.…”
Section: Methodsmentioning
confidence: 99%
“…For example, keratinocyte growth factor and sex steroid ablation have been reported to improve thymopoiesis by restoration of the functions of thymic epithelial cells [8][9][10][11][12][13]. Transplantation of cultured thymus fragments has been used to provide the thymic microenvironment for T-cell regeneration in patients and experimental animals with T-cell deficiencies or as a method for the induction of tolerance in organ transplantation [7,[14][15][16][17]. Studies on thymus organogenesis in the murine embryo have indicated that both the cortical and medullary epithelial cells arise from a common progenitor population [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The thymic epithelial progenitors (TEPs) in the embryonic thymus have been reported to be MTS24+ cells due to the finding that purified MTS24+ cells can reconstitute a functional thymic epithelial microenvironment capable of supporting T-cell development in vivo (Markert et al, 2003;Hong et al, 1979). However, another recent study showed that thymic architecture could be formed in vivo by a large number of MTS24-cells (Yamada et al, 2000). While the expression of a common surface marker on these progenitor cells remains controversial, ontogenetic analysis of epithelial cells during thymic development has shown that TEPs co-express cytokeratins (k) 5 and K8,, then proliferate and differentiate into mature K5-K8+ cTECs and K5+k8-mTECs Klug et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Administration of keratinocyte growth factor or sex steroid ablation has been shown to increase the number of TECs, resulting in enhanced thymopoiesis (Kelly et al, 2008;Min et al, 2002;Min et al, 2007;Alpdogan et al, 2006). Additionally, transplantation of cultured thymus fragments has been used to provide the thymic microenvironment for T-cell regeneration in patients and experimental animals with T-cell deficiencies or as a method for the induction of tolerance in organ transplantation (Markert et al, 2003;Hong et al, 1979;Yamada et al, 2000;Kamano et al 2004). However, the applications of cultured thymus fragments are limited by tissue availability.…”
Section: Introductionmentioning
confidence: 99%